2017
DOI: 10.1002/1878-0261.12078
|View full text |Cite
|
Sign up to set email alerts
|

K‐Ras mutation and amplification status is predictive of resistance and high basal pAKT is predictive of sensitivity to everolimus in biliary tract cancer cell lines

Abstract: Advanced biliary tract cancer (BTC) has a poor prognosis and limited treatment options. The PI3K/Akt/mTOR signalling pathway is hyperactivated in a subset of BTCs, and clinical activity of the mTOR inhibitor everolimus has been observed in some patients with BTC. The goal of this study was to identify biomarkers predictive of everolimus response. Twenty BTC cell lines were assessed for everolimus sensitivity with a spectrum of growth inhibitory responses observed. Molecular biomarkers of sensitivity and resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…In this regard, we recently observed that BTC cell lines with high basal p-AKT expression respond preferentially to everolimus in vitro. 28 Similarly, renal and gastric cancers harbouring higher basal activation of the PI3K/AKT/mTOR pathway have also been reported to show improved response to everolimus. 29,30 In comparison, in the current study we failed to observe an association between the levels of a number of IHC readouts of PI3K/AKT/mTOR pathway activity and benefit to everolimus treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, we recently observed that BTC cell lines with high basal p-AKT expression respond preferentially to everolimus in vitro. 28 Similarly, renal and gastric cancers harbouring higher basal activation of the PI3K/AKT/mTOR pathway have also been reported to show improved response to everolimus. 29,30 In comparison, in the current study we failed to observe an association between the levels of a number of IHC readouts of PI3K/AKT/mTOR pathway activity and benefit to everolimus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of KRAS amplification and mutation status. Mutations in KRAS have been associated with resistance to everolimus in BTC cell lines, 17 and in patients with colorectal cancer who are treated with this agent. 25 Sanger sequencing of KRAS (exons 2 and 3) identified only two patients harbouring KRAS mutations, of whom one was the patient with ampullary carcinoma with intestinal differentiation who also harboured a PIK3CA (E545K) mutation.…”
Section: Biomarker Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“… 58 , 66 Mutations in PIK3CA are frequent in GBC (8–13%). 57 , 67 PI3K/AKT/mTOR often signals downstream of ErbB/HER and preclinical studies suggest activity of PI3K/AKT/mTOR inhibition in BTCs, 68 , 69 although clinical studies are scarce. PI3K inhibitors in clinical development such as BKM-120 and taselisib may be relevant to BTCs.…”
Section: Pi3k/akt/mtormentioning
confidence: 99%